Analysis of Bondowoso Regency Government’s Advertising Strategy in Building Sport Tourism Branding - Junaedi, Rusli Akhmad (P3M Politeknik Negeri Jember, 2025)
This article aims to analyze the Bondowoso Regency Government’s advertising strategy in building a sports tourism image and evaluate its success in increasing tourist visits and community participation. Using a qualitative approach with a case study, data were collected through in-depth interviews, direct observation, and documentation studies. The results showed that digital media, such as social media and online platforms, effectively delivered promotional messages and strengthened the destination’s image. Regular events such as the Bondowoso Night Run 2025 and other sports activities act as promotional icons and tourist attractions. This strategy has successfully increased community participation and attracted domestic and international tourists, strengthening Bondowoso’s position as an innovative and competitive sports destination. However, challenges remain related to the lack of innovation in digital promotion and the optimal utilization of technology. Therefore, this study recommends developing innovative digital content and a study of the impact of tourism experience to improve the effectiveness of future promotional strategies. These suggestions are expected to support the development of sustainable and adaptive sports tourism.